Linking the small-scale relativistic winds and the large-scale molecular outflows in the z = 1.51 lensed quasar HS 0810+2554. Issue 1 (3rd April 2020) - Chartas, G; Davidson, E; Brusa, M; Vignali, C; Cappi, M; Dadina, M; Cresci, G; Paladino, R; Lanzuisi, G; Comastri, A
ABSTRACT: We present Atacama Large Millimeter/submillimeter Array (ALMA) observations of the quadruply lensed z = 1.51 quasar HS 0810+2554 which provide useful insight on the kinematics and morphology of the CO molecular gas and the ∼ 2 mm-continuum emission in the quasar host galaxy. Lens modelling of the mm-continuum and the spectrally integrated CO(J = 3→2) images indicates that the source of the mm-continuum has an eccentricity of e ∼ 0.9 with a size of ∼1.6 kpc and the source of line emission has an eccentricity of e ∼ 0.7 with a size of ∼1 kpc. The spatially integrated emission of the CO(J = 2→1) and CO(J = 3→2) lines shows a triple peak structure with the outer peaks separated by Δ v 21 = 220 ± 19 km s −1 and Δ v 32 = 245 ± 28 km s −1, respectively, suggesting the presence of rotating molecular CO line emitting gas. Lensing inversion of the high spatial resolution images confirms the presence of rotation of the line emitting gas. Assuming a conversion factor of αCO = 0.8 M⊙ (K km s −1 pc 2 ) −1 we find the molecular gas mass of HS 0810+2554 to be M Mol = (5.2 ± 1.5)/μ32 × 10 10 M⊙, where μ32 is the magnification of the CO(J = 3→2) emission. We report the possible detection, at the 3.0–4.7σ confidence level, of shifted CO(J = 3→2) emission lines of high-velocity clumps of CO emission with velocities up to 1702 km s −1 . We find that the momentum boost of the large-scale molecular wind is below the value predicted for an energy-conserving outflow given the momentum flux observed in the small-scale ultrafast outflow.